Analysis of the Implementation of the Attitude of National Defense and Indonesian National Resilience in Students - Sembiring, Nanda br; Handayani, Gaty Sry; Gaol, Ayunita Lumban; Afsah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the response and ability of students in implementing the attitude of defending the country and Indonesian national resilience among the ranks of students. The method used is a quantitative method which is data collection based on the results of a questionnaire filled out directly by respondents. Data collection techniques are obtained from observations of students. The sample in this study was 20 PGSD students at Medan State University. The results of the study showed that the activity of student responses to the implementation of the attitude of defending the country and Indonesian national resilience was very good. In conclusion, awareness of defending the country is essentially a willingness to serve and sacrifice for the country.